Expurgo de docentes na lógica da Doutrina de Segurança Nacional: o caso da FURG (1969-1977) - Kantorski, Leonardo Prado (2011)
The dictatorship military-civil in Brazil, by means of your authoritarian politics, caused numerous impacts on the country's social structure. How could no longer be one of the sectors of society that has not been immune to the actions of legal state violence, was public higher education. The impact of this interference in the educational field has different characteristics according to the peculiarities of each institution. This paper addresses the process of purging occurred in FURG teaching in a time window between 1969, year of foundation of the Federal University of Rio Grande, and 1977, the purges year. The study, in adduce elements wich the results were the purge of teachers in FURG, contributes for the understanding the politics of authoritarian dictatorship in the intellectual circles. The great importance of the memory of the faculty for this research is to establish a significant source, capable of assisting in the understanding of the peculiarities. They outlined the process of purging of teachers at the University, thus contributing to the exposure of events that currently are not part of the official History of FURG